PENENTUAN OBJEK WISATA, OBJEK KULINER SERTA AKOMODASI DISEKITAR PENGGUNA DIKOTA PALEMBANG DENGAN MENGGUNAKAN ALGORITMA EUCLIDEAN DISTANCE - Filian Falanda; Rendra Gustriansyah; Hartini Hartini (Jurnal Informatika Global)
Palembang is the capital of South Sumatera province, Which has been well known of the great kingdom of sriwijaya. therefore this places been one of destination people tourism which full of the historical and culture heritage. In generally tourism has definition as a journey in which short stay are made at a number of places, and traveler finally return to his or her own place.A Tourism is supported by some elements such as accommodation, food objects and tourism objects. While many tourism object hard to get to access a lot of information about tourism that make the tourists confused to find because of the lack of information for traveling, therefor to overcome these problems the writer made an application to the tourism city of Palembang-based android that can help determine the existing tourist destinations around the users in town by using Euclidean Distance algorithm.The application is accessed through the support of mobile Google Map and Google API using GPS (Global Positioning System) which was built on the Android platform. In the system of the author will be built using the model Prototype. This method is the one of development of the system where the results of the analysis division applied directly into a model without having to wait for the completion of the entire system is analyzed. As well as the role of distance euclidean algorithm which can be used to calculate the distance between the object and the tourism and compare the results of the calculations of some object, so it can provide recommendations about the objects.Keywords: Algoritm, Android, EuclideanDistance,Tourism